Effectiveness of Sanctions Regime towards Iran - R A Ustinov (Vestnik RUDN. International Relations, 2011)
The UN Security Council has adopted six Resolutions regarding the Iranian nuclear programme. Four of theses Resolutions impose sanctions on Iran with each next Resolution implying broader and tougher sanction measures. Though the scope of introduced sanctions cannot but to have a certain impact on the economic development of the country, Iran doesn't seem to succumb to the requirements of the international community in respect to its nuclear programme. May be it is a high time to develop a comprehensive and smart approach to deal with this issue.